Mediating Role of Resourcefulness in the Relationship Between Illness Uncertainty and Poststroke Depression - Liu, Jing; Wang, Hongxia; Lin, Beibei; Ning, Liuqiao; Liu, Danman; Li, Jufang (Frontiers in Psychology, 2022)
Objectives: To examine the association between illness uncertainty, resourcefulness and poststroke depression and identifies whether stroke patients’ resourcefulness plays a mediating role in the relationship between illness uncertainty and poststroke depression. Methods: A cross-sectional study was conducted from September 2020 to April 2021. A convenience sample of 355 stroke patients was recruited. A general characteristic questionnaire, the Mishel Uncertainty in Illness Scale, the Resourcefulness Scale, and the Patient Health Questionnaire-9 were used to obtain data. Descriptive analysis, Pearson correlation analysis, and mediation analysis with the PROCESS macro were used to analyze the data. Results: Illness uncertainty, resourcefulness and poststroke depression were significantly related to each other. Resourcefulness partially mediated the relationship between illness uncertainty and poststroke depression. Conclusions: Illness uncertainty increased the risk of poststroke depression. Resourcefulness mediated the relationship between illness uncertainty and poststroke depression. Interventions designed to reduce illness uncertainty and enhance resourcefulness may contribute to the prevention and improvement of poststroke depression.